Anomalous effects of radioactive decay rates and capacitance values measured inside a modified Faraday cage: Correlations with space weather. (19th May 2017) - Scholkmann, F.; Milián-Sánchez, V.; Mocholí-Salcedo, A.; Milián, C.; Kolombet, V. A.; Verdú, G.
Abstract: Recently we reported (Milián -Sánchez V. et al., Nucl. Instrum. Methods A, 828 (2016) 210) our experimental results involving 226 Ra decay rate and capacitance measurements inside a modified Faraday cage. Our measurements exhibited anomalous effects of unknown origin. In this letter we report new results regarding our investigation into the origins of the observed effects. We report preliminary findings of a correlation analysis between the radioactive decay rates and capacitance time series and space weather related variables (geomagnetic field disturbances and cosmic-ray neutron counts). A significant correlation was observed for specific data sets. The results are presented and possible implications for future work discussed.